Respuesta :

Assuming that we are solving in terms of n.


Start by distributing:

2(n + 5)

(2*n) + (5*2)

2n + 10 = -2


Subtract 10 to start toward isolating your variable:

2n = -12


Divide by two to finish solving:

n = -6

Answer:

n=-6

Step-by-step explanation:

2(n+5)=-2

distribute the 2 to the numbers in the parentheses:

2n+10=-2

Get the n factor alone, subtract 10 from both sides:

2n=-12

Now you just want the n alone so you are going to use the inverse operation on 2n to both sides: 2n/2=-12/2

n=-6

If you need any other help i would be glad to assist.

ACCESS MORE